The Relationship between Work-life Integration and Well-being of E-hailing Drivers : Mobile Technology as Moderator - Nur Farah Dayana, Suhaimi (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is aimed at finding the relationship between the work-life integration and well-being (life satisfaction and job satisfaction) among e-hailing drivers and whether mobile technology moderates the relationship between the two variables. This research was done by using quantitative method where the data were collected by using questionnaires as the instrument. The data was collected form 60 samples who work as e-hailing drivers in Kuching, Sarawak. The data were then analysed by using both descriptive and inferential statistics. Besides, Spearman Correlation test procedure was used to measure the relationships between the independent variables and dependent variables. The findings have shown there is a strong positive and significant relationship between work-life integration and well-being of the e-hailing drivers. It was also found that the mobile technology does not moderates the relationship between work-life integration and wellbeing. As such, the researcher has recommended a focus on the study that may guide the organizations and future researches.